(untitled) (Global Journal of Medical Research, 2015)
The scaffold-based tissue engineering of bones is an extremely promising concept with regard to the regeneration of major bone defects due to trauma, tumour or developmental abnormalities as well as for the treatment of pseudo-arthroses. The in vivo testing of implants is a significant phase in the development of specimens for the clinical application of suitable scaffolds. The collection of an optimal amount of information from these initial -clinical -tests demands, ideally, the most diagnostically conclusive studies possible. We tested the procedure of flat panel volumetric computer tomography (fpvCT) thus far virtually untried in the area of bone tissue engineering for the in vivo evaluation of small animal experiments and compared it with other methods (projection radiography, micro-CT, histology).